The Impact of Corporate Governance, Ownership Structure, and Cash Flow on the Value of the Companies Listed on the Iraqi Stock Exchange - Diana Neamah Abdulrazzaq; Mehdi Arab Salehi; Leila Torki (Iranian Journal of Accounting, Auditing & Finance, 2024)
Stock price garners considerable attention from internal (financial and executive managers) and external (creditors and shareholders) users. Shareholders invest in the company’s stock to gain profitable returns. Cash holding level is among the most important determinants of firm value (stock price). Managers might invest the excess cash in non-profitable projects and reduce the firm value. However, studying corporate governance mechanisms and ownership structure can control such managerial behaviors. Therefore, this study investigates the impact of corporate governance, ownership structure, and cash holding on firm value. The sample comprises 35 companies listed on the Iraq Stock Exchange via a systematic sampling method. Multiple regression models and panel data analyzed the data. Findings show that corporate governance and cash holding affect the value of Iraqi companies, but ownership structure does not significantly affect firm value. To the extent of our knowledge, this is the first study investigating the impact of corporate governance, ownership structure, and cash flow on the value of Iraqi companies. Despite earlier studies, this study uses the composite index to evaluate corporate governance.